Analisis Kejadian Tuberkulosis Paru Dan Faktor Risikonya di Kecamatan Pamulang, Kota Tangerang Selatan - Fenita Purnama Sari Indah; Ita La Tho (Edu Masda Journal, 2019)
Pulmonary tuberculosis is a global health problem that has been a global concern for the past two decades. According to the Indonesian Ministry of Health in 2016, Banten Province has an estimated number of lung patients with tuberculosis reaching 40,227 people, but has been detected or recorded as many as 16,608 people, with the first increase in the number of sufferers in South Tangerang reaching 2,089 people. In the City of South Tangerang in 2015 there were 5,246 suspected TB pulmonary cases, of which 735 cases were positive smear pulmonary TB cases. The purpose of this study was to identify factors associated with the incidence of pulmonary tuberculosis in Pamulang Subdistrict, South Tangerang City. This research is a quantitative study, using analytic survey research methods with cross sectional approach. The number of samples obtained was 210 respondents. Because this research uses the Rapid Survey method with sample criteria of 210 to 300 respondents. The results of this study indicate that there is no significant relationship between knowledge about pulmonary tuberculosis with the incidence of pulmonary tuberculosis in respondents (p value = 0.23> 0.05) and there is a significant relationship between attitude and the incidence of pulmonary tuberculosis (p value = 0,000 <0, 05), with an OR of 3.237. That is, the attitude about the prevention of pulmonary tuberculosis that is not good will increase the risk of the occurrence of pulmonary tuberculosis by 3x compared with the attitude regarding the prevention of pulmonary tuberculosis is good.